Research progress on self-management ability of patients with urostomy (泌尿造口患者自我管理能力的研究进展) - JIANG Cuirong (蒋翠荣); MENG Yuemei (蒙月梅); SONG Zhike (宋之珂); YAO Li (姚莉) (中西医结合护理)
Self-management ability plays vital role in quality of life and rehabilitation of patients with urostomy. This study provides an overview of the research progress on self-management ability of patients with urostomy. Through comprehensive literature collection and analysis, this study aims to summarize the significance, influencing factors and strategies of improving elf-management ability, provide reference for clinical practice and improve self-management ability of patients by conducting relevant education and training to cultivate their health awareness and self-management skills. (自我管理对于提高泌尿造患者的生活质量和康复效果至关重要。本文通过对泌尿造口患者自我管理能力的研究进展进行概述, 总结泌尿造口患者自我管理的重要性、影响泌尿造口患者自我管理能力的因素以及提升患者自我管理能力的策略, 旨在为临床医生和护士提供可靠指导, 帮助医务人员更好地协助患者进行自我管理, 提高患者的康复效果和生活质量。)